INTEGRATING ETHICAL AND FAITH BASED VALUES IN SOCIAL LIFE : A Hadith Perspective of Shaykh Nawawi al-Bantani in Qāmi’ al-Ṭuġyān - Fahmi Andaluzi; Irfan Padlian Syah; Abdul Fatah (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This Morality is an important part of the teachings of Islam where morality is included in the scope of faith and is classified as a discussion of monotheism. This article seeks to examine the discussions of morality in the book Qāmiʻ al-Ṭuġyān by Sykeh Nawawi al-Bantani The method used in searching for data in this study is the library research method by collecting primary and secondary reference sources, the author uses the book Qāmiʻ al-Ṭuġyān as a primary source while for secondary sources use books or other articles that are relevant to the discussion. For the discussion in this article, the author uses a descriptive-analytical method, namely by first describing the discussion of morality in the book Qāmiʻ al-Ṭuġyān and then analyzing the data obtained. The results of this study show that morality is a very important part of Islamic teachings, in the book Qāmiʻ al-Tuġyān morality includes two important themes, first, a person's attitude towards Allah SWT and His Messenger, namely by carrying out his commands and staying away from his prohibitions and carrying out his sunnahs, second, morality is also a person's attitude in social life, namely having a gentle heart, full of affection, being kind to neighbors, honoring guests and the community.